Virtual source aperture imaging with auto-focusing of unknown complex geometry through dual layered media. (September 2018) - Hoyle, Ewan; Sutcliffe, Mark; Charlton, Peter; Rees, John
Abstract: In this paper, a Virtual Source Aperture (VSA) surface mapping technique applicable for ultrasonic inspection of components with complex geometry through dual layered media is described. Assuming the first medium is free of significant discontinuities, the first echo arrives from the boundary between the two mediums. The surface is described by the tangent to a family of ellipses constructed using the time of the first echo from the VSA data set and the known positions of the transmitters and receivers. The Total Focusing Method, using Fermat's principle to account for refraction, is used to generate fully focused images of the test specimen interior. Using this technique, it is possible to obtain surface information and generate an image with as little as a single firing of the ultrasonic array, which will be of significance when ultra fast ultrasonic inspection is necessary. The method is tested on a series of surfaces with varying geometry and is shown to successfully image and position a series of side drilled holes within each specimen.